Foreman Performance Motivation Factors Analysis in Construction Projects - JAMES THOENGSAL; M. Tumpu (Kirana Publisher (KNPub), 2023)
Work motivation for workers in a project can be considered simple and can also be a complex problem, because basically humans are easy to motivate by giving what they want. Furthermore, motivation is a process as the first step for someone to take action due to physical and psychological deficiencies or in other words, it is an encouragement shown to fulfill certain goals. If this condition does not occur, it will reduce worker work motivation and will result in decreased worker performance. This research aims to determine the level of needs that influence the motivation of construction foremen and analyze the motivational factors that influence the motivation of construction foremen. The method used by researchers was by distributing questionnaires to 15 foremen who were used as respondents for construction project research in Pangkep, as well as conducting interviews with three or four project foremen. Based on the research results, it was found that 5 factors have the most influence on the motivation of construction project foremen in Pangkep Regency in general, namely: Of the 23 motivation factors, there are 5 factors that have the most influence on the motivation of construction project foremen in general, namely: (1) adequate wages/salaries , (2) good workplace facilities, (3) payment received on time, (4) Good relationships with fellow workers, (5) good work direction program.